Female reception of masculine picture of the world in modern Ukrainian novels (on the material of “Egoist” by Maryna Grymych) - Башкирова, Ольга Миколаївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The ways of artistic modeling of masculine hero’s picture of the world in the novel “Egoist” by Maryna Grymych are investigated in this article. The row of main artistic tendencies which characterize modern literary process as the unique field of cooperation of carriers of different gender mentality are traced. The specific of artistic actualization of basic mental consciousness’ constants (village – city, elite – people) are educed. The artistic principles of creation of personality’s conception based on the postmodernist poetics’ main points are the subject of special interest. The facilities by means of which the author sets the dialogic connections between the artistic structure of her novel and modern feministic theory are demonstrated in the investigation.